Proteomic Profiling of Secreted Proteins for the Hematopoietic Support of Interleukin-Stimulated Human Umbilical Vein Endothelial Cells. Issue 7 (July 2013) - Bal, Gürkan; Kamhieh-Milz, Julian; Sterzer, Viktor; Al-Samman, Muhammad; Debski, Janusz; Klein, Oliver; Kamhieh-Milz, Sundrela; Bhakdi, Sucharit; Salama, Abdulgabar
Human umbilical cord vein endothelial cells (HUVECs) secrete a number of factors that greatly impact the proliferation and differentiation of hematopoietic stem and progenitor cells (HSPCs). These factors remain largely unknown. Here, we report on the most comprehensive proteomic profiling of the HUVEC secretome and identified 827 different secreted proteins. Two hundred and thirty-one proteins were found in all conditions, whereas 369 proteins were identified only under proinflammatory conditions following IL-1β, IL-3, and IL-6 stimulation. Thirteen proteins including complement factor b (CFb) were identified only under IL-1β and IL-3 conditions and may potentially represent HSPC proliferation factors. The combination of bioinformatics and gene ontology annotations indicates the role of the complement system and its activation. Furthermore, CFb was found to be transcriptionally strongly upregulated. Addition of complement component 5b-9 (C5b-9) monoclonal antibody to the stem cell expansion assay was capable of significantly reducing their proliferation. This study suggests a complement-mediated cross-talk between endothelial cells and HSPCs under proinflammatory conditions.